2013
DOI: 10.5812/numonthly.11667
|View full text |Cite
|
Sign up to set email alerts
|

Different Aspects of Fatigue Experienced by Patients Receiving Maintenance Dialysis in Hemodialysis Units

Abstract: BackgroundFatigue, a common symptom reported by patients receiving dialysis, is a multidimensional and subjective experience which is readily understood by individuals but difficult to measure.ObjectivesThis study was performed to identify the prevalence of differential aspects of fatigue among patients receiving maintenance dialysis.Patients and MethodsThe cross-sectional study was conducted in two hemodialysis wards in Tehran with a sample of 163 participants. In this study, the multidimensional fatigue inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 13 publications
6
14
0
3
Order By: Relevance
“…Thus, our results are in accordance with a cross-sectional study from the Netherlands [15] of 841 patients with RA reporting a high score on all the five fatigue domains included in the MFI-20. In addition, although no direct comparison with other clinical subpopulations or healthy individuals was made in this study, the stated scores correspond with MFI-20 values reported in other clinical populations [35][36][37]. In comparison, the general population [38,39] including the Danish population [40] rated fatigue scores that were skewed toward the absence of fatigue on the MFI-20.…”
Section: Discussionsupporting
confidence: 62%
“…Thus, our results are in accordance with a cross-sectional study from the Netherlands [15] of 841 patients with RA reporting a high score on all the five fatigue domains included in the MFI-20. In addition, although no direct comparison with other clinical subpopulations or healthy individuals was made in this study, the stated scores correspond with MFI-20 values reported in other clinical populations [35][36][37]. In comparison, the general population [38,39] including the Danish population [40] rated fatigue scores that were skewed toward the absence of fatigue on the MFI-20.…”
Section: Discussionsupporting
confidence: 62%
“…Regarding to occupation status, results indicated that a highest percentage of the study sample are (unemployed, no working, retired, and house wife), and the accounted (78%). This result agree with a study done by Vajihe et al , who found that the highest percentage (42%) of the study sample is don't work (6) . In regarding to monthly income, the majority of the study sample are within the insufficient monthly income, based on that and according to the diseases related cost of care statistics, individual as well, especially in our country as a developing one who that lives under the shadows of the global financial crisis.…”
Section: Discussionsupporting
confidence: 82%
“…And they are accounted for (23) patients with percent (44%) with age mean (51.4) years. This result agree with Amy et al , that show the majority of study sample with mean age (52) (5) .and agree with Vajihe et al , that show the majority of study sample with mean age (54) (6) . This might because of prevalence of diabetes type 2 and long standing uncontrolled hypertension among these age group ( researcher), this result supported by Alashek et al, who sated that diabetes and hypertensive nephropathy were more common causes of end stage renal disease (ESRD) in patients mean age (49) years (7) .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The high prevalence of symptoms such as fatigue (11), anorexia (12), sleep disorders (13), nausea and vomiting (14), peptic ulcer disease (15), itching (16), blood coagulation disorders (17), hyperparathyroidism (18), infection (19), dysgeusia (20), and blood pressure fluctuations due to inadequate dialysis can undermine the quality of life. Previous studies pinpointed several factors as barriers to adequate dialysis, namely patient -related factors (e g, hypotension, intradialytic symptoms, treatment time missed due to noncompliance or transportation problems, duration < 4 hours, blood flow rate (BFR) < 350 mL/minute, patient weight > 100 kg, and delivered BFR 50 mL/minute less than the prescribed BFR) and technical factors (e g, dialysis prescription, type of vascular access, clotting, and dialyzer reuse) (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%